The intersection between climate change and capitalism: the case of West Papua’s ecocide - Karume, Tracy (Daystar University, School of Communication, 2025)
The global economic expansion and capitalism are integral driving forces of climate change often experienced disproportionately. Efforts to mitigate climate change continue to fail as the poorest countries suffers the most due to their limited capability to adapt. Pollock (2020) denotes that the growth of economic development has largely contributed to increased consumption of natural resources, pollution and loss of biodiversity. More than 90 West Papua’s indigenous communities and political organizations have been calling for the boycott of Nestle products due to massive lands of rainforests being cleared for agriculture (Gayle, 2025). Guided by Eco-Marxism theory, this qualitative study aims to examine the relationship between climate change and capitalism in the case of West Papua against Nestle. This study will use document analysis and thematic analysis to examine two objectives. These are; to examine the influence of capitalist practices on environmental degradation in West Papua and to analyze the socio-economic consequences of climate change on indigenous communities in West Papua. The findings of the study will be analyzed thematically, in line with the objectives and the theoretical underpinning of the study. This study is integral and timely due to the increased struggle by communities in the Global South against climate injustice. It also highlights the urgency to interrogate exploitative development archetypes in the Global South.
Conference Paper
Keywords: Capitalism climate change climate injustice ecocide indigenous communities